Faktor yang Berhubungan dengan Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Fe - Rauda Rauda; Pratiwi Nasution; Novy Ramini Harahap; Mila Syari; Nabila Safitri (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
Anemia in pregnancy or often called potentional danger to mother and child is a condition of iron deficiency in pregnant women. Anemia in pregnancy has a hemoglobin level <11% in the first and third trimester while in the second trimester the hemoglobin level is <10.5%. WHO data shows that anemia occurs in almost 2 billion people worldwide suf Fering from iron deficiency and 50% of them are pregnant women. The purpose of this study was to determine the factors associated with compliance of pregnant women in consuming Fe tablets. The research method was conducted with a quantitative design with a cross-sectional approach. The population was all third trimester pregnant women at the mardianum clinic and the sample in this study used a total population of 34 people. Data were collected by questionnaire and patient register. Data analysis using chi-square test. The results of this study showed that most mothers' knowledge was poor at 61.8%, negative maternal attitudes at 58.8%, poor maternal family support at 64.7%, and the role of health workers was poor at 58.8% and non-compliant at 64.7%. This study states that knowledge, attitude, family support and the role of health workers are factors associated with the level of compliance of pregnant women in taking Fe tablets.